Effectiveness on Cross Border Trades Between Thailand, Lao Pdr, Vietnam and China - Mohamad Ghozali Hassan; Pichit Prapinit; Radasa Netsangsee; Mustakim Melan (International Journal of Supply Chain Management, 2020)
This study investigates on the effectiveness of present cross border trades at Loei District checkpoint of North East in Thailand to Lao PDR, Vietnam and China.  It also examines on the regional economic connectivity of supply chain in Thailand and neighboring countries especially for Greater Mekong Sub-Region (GMS) Programme. It also explores on the readiness of road infrastructure, cross border facilities, customs, regulations, usage of technology and other obligations to the wider scope.  It also focuses on the trading of retail goods for household consumption and wholesale merchandises. This is a quantitative research and the surveys were conducted among 300 respondents which include transporters, entrepreneurs, government, regulatory bodies and other stakeholders. The findings of the research revealed on the certain actions need to be taken for future improvement at border checkpoint. This includes on improvement on the of customs inspection, readiness of the infrastructure, suitability in rules and regulations and the understanding of usage of technologies in the department of Immigration, Customs, Quarantine and Security (ICQS) at cross border areas.